1999
DOI: 10.1046/j.1439-0507.1999.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CHROMagar Candida for rapid screening of clinical specimens for Candida species

Abstract: CHROMagar Candida is a new differential culture medium that allows selective isolation of yeasts and simultaneously identifies colonies of Candida albicans, Candida glabrata, Candida tropicalis and Candida krusei. We evaluated this medium and compared it with a reference medium, Sabouraud glucose agar, for the presumptive identification of yeast species isolated directly on the medium from 1150 clinical specimens. A total of 731 specimens showed no growth, 299 isolates (70.2%) showed growth to the same extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
2
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 17 publications
(18 reference statements)
10
40
2
3
Order By: Relevance
“…CHROM agar Candida identified all C.albicans, C.tropicalis, C.glabrata and C. krusei correctly, which correlated with findings of Willinger B. et al, [13] Yucesoy M et al, [14] Momani OM et al, [15] and Gultekin et al, [16]. But in the study of Guelfand L, 100% C.albicans, 92% C. tropicalis, 91% C. krusei were identified and in the study of Houang et al, [17] 100% of C. albicans, C.tropicalis, C. Krusei and 82% of C.glabrata were identified correctly on CHROM agar candida.…”
Section: Prevalencesupporting
confidence: 87%
“…CHROM agar Candida identified all C.albicans, C.tropicalis, C.glabrata and C. krusei correctly, which correlated with findings of Willinger B. et al, [13] Yucesoy M et al, [14] Momani OM et al, [15] and Gultekin et al, [16]. But in the study of Guelfand L, 100% C.albicans, 92% C. tropicalis, 91% C. krusei were identified and in the study of Houang et al, [17] 100% of C. albicans, C.tropicalis, C. Krusei and 82% of C.glabrata were identified correctly on CHROM agar candida.…”
Section: Prevalencesupporting
confidence: 87%
“…In present study C. krusei and C. glabrata both showed 100% sensitivity and 100% specificity on chromogenic agar media which is higher than that of above mentioned study. Willinger et al reported 98% sensitivity and 95% specificity for C. glabrata on chromogenic agar media 12 . They found 100% sensitivity and 100% specificity for C. krusei on chromogenic agar media which is in consistent with the findings of present study.…”
Section: Discussionmentioning
confidence: 99%
“…In present study C. parapsilosis and C. guilliermondii could not be differentiated from each other on chromogenic media. Though Willinger et al have solved this confusion by giving special attention to the evidence of pale edges on pink colonies of C.glabrata, but we couldn't appreciate this property for differentiation from other species 12 . Thirty three isolates of C. albicans were identified by germ tube test which were similar to finding of carbohydrate assimilation test.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have already substantiated this finding, reporting sensitivity & specificity of 98-100 & 100 % respectively [6,[9][10][11][12][13][14]. C. dublinensis was found to give characteristic dark green colonies, distinctive from those of C. albicans.…”
Section: Utility Of Chromagar Tm Candida (Cc)mentioning
confidence: 95%
“…Review of literature, also shows conflicting reports about the sensitivity of C. krusei detection on CC. Some studies have claimed a 100% sensitivity and specificity in their study [6,9,13]. However, there could be a bias towards CC in some studies, as the authors have used API confirmed isolates for evaluating CC, and not looked at CC as the first line of identification.…”
Section: Utility Of Chromagar Tm Candida (Cc)mentioning
confidence: 99%